Google Suite: An Integrated IT application for Improved Business Efficiency - Mahapatra, Tania; Chopra, Meenu; Mahapatra, Cosmena (International Journal of Computer Sciences and Engineering, 2025)
Google Suite is a package of integrated cloud based services that provide an organization a novel way to work together online. The advantages are not just limited to personalized business Gmail and instant chat messaging but extend to real time document collaboration, social media, video conferencing, increased cloud storage capacity, eDiscovery, log analysis, audit reports, enhanced security controls & data loss prevention. It is a set of applications that can prove invaluable to the organisation as it facilitates communication & information sharing for quick decision making and follow ups. With this, G Suite has emerged as a competitor to MS Office 365 which offers similar package benefits to users. Still, the innovative model of G Suite proves more promising when it comes to versatility, cost efficiency and feasibility.